Análise paramétrica de antenas anelares de microfita - Oliveira, Francisco José Dantas de (Universidade Federal Rural do Semi-Árido, 2019)
Wireless communication systems have been developing continuously. Due frequent higher communication speed demands and fitting to several services in various frequencies, a lot of implementation methods are being studied to solve problems and increasing antennas versatility, reliability and scalability. This paper aims to perform a study of microstrip ring antennas behavior based on a standard planar microstrip antenna projected to the frequency range of 5.8 GHz. Changes on metallic structure were made, simulating with computational software and developing some ring microstrip antennas prototypes, checking your radiation patterns and gain acquired from each one, comparing the similarity between simulated and measured built antennas results. A vector network analyzer and an anechoic chamber were used to measure the antennas parameters. The obtained results were analyzed with computational programs aid in order to compare datas, create charts and make visualization and results understanding easier. It was possible to certify, with acquired results, that most of antennas presented several resonant modes and, is some cases, there was a tendency of bandwidth raising and reflection coefficient falling as soon as the frequency was getting increased
Keywords: Antenas de microfita; Antenas anelares; Antenas planares; Microstrip antennas; Ring antena; Planar antenna; ENGENHARIAS::ENGENHARIA ELETRICA